Implementation of The Musyarakah Agreement in the Profit Sharing System of Chicken Farming (Case Study of Selayang Village, Selesai District, Langkat Regency) - Aura Dila; Ahmad Zuhri Rangkuti (Fox Justi : Jurnal Ilmu Hukum, 2025)
This research is motivated by a collaborative system in poultry farming, which has been seen rapid growth but still faces major challenges, particularly limited capital availability . The profit- sharing partnership system requires a large area of land, similar to partnerships in cattle, goat, and chicken farming. Such a partnership takes place in Selayang Village, Selesai Subdistrict, Langkat Regency, particularly in the profit- sharing system applied to the chicken farm owned by Mr. Iswandi. This study employs a qualitative approach using field research methods, tailored to the main objective of describing and implementing the application of a profit- sharing system in poultry farming based on the Musharakah contract . The findings show that Musyarakah is a cooperative agreement between two or more parties in a specific business where each party contribute capital, and profits and risks are shared according to a mutual agreement . In this poultry farming profit- sharing system, there is no demand for equal division of labor ; instead, each party is responsible for the tasks agreed upon at the start of the contract . In this case, PT Indonesia Agrinusa – Binjai is responsible for assisting the farmer throughout the chicken rearing period until harvest and also plays a role in marketing the products . Meanwhile, the farmer, Mr. Iswandi, is responsible for maintenance the chicken throughout the duration of the partnership .